2016
DOI: 10.1093/mutage/gew019
|View full text |Cite
|
Sign up to set email alerts
|

Mouse models for radiation-induced cancers

Abstract: Potential ionising radiation exposure scenarios are varied, but all bring risks beyond the simple issues of short-term survival. Whether accidentally exposed to a single, whole-body dose in an act of terrorism or purposefully exposed to fractionated doses as part of a therapeutic regimen, radiation exposure carries the consequence of elevated cancer risk. The long-term impact of both intentional and unintentional exposure could potentially be mitigated by treatments specifically developed to limit the mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 244 publications
2
28
0
Order By: Relevance
“…[21,22] Mouse studies of radiation effects on tumor biology have increased the field knowledge about the effect on the tumor microenvironment, including cytokine and immune cell response to radiation which affects the overall tumor response. [23,24] conclusIon Radiotherapy alone had the least damaging effect on the Ehrlich's ascetic tumor cells. Such therapeutic responses may also be found in human neoplasia of various kinds, since the biology of neoplasia remains the same everywhere.…”
Section: Discussionmentioning
confidence: 96%
“…[21,22] Mouse studies of radiation effects on tumor biology have increased the field knowledge about the effect on the tumor microenvironment, including cytokine and immune cell response to radiation which affects the overall tumor response. [23,24] conclusIon Radiotherapy alone had the least damaging effect on the Ehrlich's ascetic tumor cells. Such therapeutic responses may also be found in human neoplasia of various kinds, since the biology of neoplasia remains the same everywhere.…”
Section: Discussionmentioning
confidence: 96%
“…Physical: irradiation γ rays and X rays Suppression of bone marrow resulting in marrow atrophy and pancytopenia. 182,[237][238][239][240][241][242][243][244] High dose: decreased splenic and thymic weights; loss of cortical thymocytes; decreased splenic CD4+ and CD8+ T cells; decreased circulating CD3+ cells. Chronic low dose: prolonged life span in mice homozygous for the lymphoproliferation spontaneous mutation (Fas lpr ); increased CD4+ cells; suppression of IL6 and IL17, and upregulation of Tregs in CIA mice; suppression of pro-inflammatory cytokines, reduction of CD8+ T cells, and induction of Tregs in murine EAE model.…”
Section: Inducers Possible Effects On the Immune And Other Systems Rementioning
confidence: 99%
“…Finally, it would be absolutely essential to decide on an appropriate biological model to use in these studies. The use of different mouse models for investigating (ionizing) radiation-induced cancers has been reviewed ( 67 ). It was suggested that the ideal mouse model possesses a low spontaneous background frequency of the desired malignancy, has a short latency period, avoids the co-development of cancers at alternative sites, and produces nearly identical tumors to the corresponding human cancer in terms of onset, progression, and underlying pathology ( 67 ).…”
Section: Future Research Needsmentioning
confidence: 99%
“…The use of different mouse models for investigating (ionizing) radiation-induced cancers has been reviewed ( 67 ). It was suggested that the ideal mouse model possesses a low spontaneous background frequency of the desired malignancy, has a short latency period, avoids the co-development of cancers at alternative sites, and produces nearly identical tumors to the corresponding human cancer in terms of onset, progression, and underlying pathology ( 67 ). But it is acknowledged that a perfect model may not exist, so the best available model would have to be used depending on the type of cancer being investigated.…”
Section: Future Research Needsmentioning
confidence: 99%